Mechanisms of hydration heat inhibitors on the early heat release process of cement - Lv, Jiaoyang; Tian, Bo; Li, Lihui; Quan, Lei (Frontiers in Materials, 2022)
We evaluated the effect of hydration heat inhibitors on the early hydration heat release process of cement and its main mineral components. We used a microcalorimetric method to determine the effect of various proportions and properties C=40% m/m hydroxydiphosphonic acid (HEDP) (1-hydroxyethylidene-1,1-diphosphonic acid) and C=40% m/m diethylene triamine pentonyphosphonic acid (DTPMPA) (diethylenetriaminepentamethylene phosphonic acid) of hydration heat inhibitors on the hydration of portland cement, tricalcium silicate, and tricalcium aluminate. We also analyzed and tested the heat release rate as well as the cumulative heat release during the hydration of cement, and its main mineral components. The hydration heat inhibitors decreased the heat release rate of cement cementitious materials by means of adsorption, chelation, precipitation, complex formation, and control of crystals of calcium hydroxide. Among these materials, the hydration heat inhibitor had the most substantial effect on the composition of tricalcium silicate clinker, reducing the peak temperature at the initial stage of hydration and delaying the occurrence time of the peak temperature. These results are pertinent to controlling and selecting the early hydrothermal release process of cement systems.